Better Work The Impact of Automation, Flexibilization and Intensification of Work - Kremer, Monique (Research for Policy, 2021)
This Open Access book provides a thorough analysis of the quality of work in the Netherlands, and suggests policy proposals to promote and facilitate good work for more people. New technology, flexibilization and the intensification of work will have significant consequences for all those who will still have jobs in the future, and - much less studied so far - for the quality of their work. Good work is essential for general well-being: for the individual's quality of life, for the economy and for society. Good work for everyone should therefore be seen as an important aspiration for companies, institutions, social partners and governments. An essential read for an international audience of academics in the field of the sociology of work, labor economics and social policy, as well as for policymakers and researchers of trade unions, and representatives of other social movements.